2019
DOI: 10.1016/j.eplepsyres.2019.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Harmonization of the pipeline for seizure detection to phenotype post-traumatic epilepsy in a preclinical multicenter study on post-traumatic epileptogenesis

Abstract: Harmonization of the pipeline for seizure detection to phenotype post-traumatic epilepsy in a preclinical multicenter study on post-traumatic epileptogenesis,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…In rats with spontaneous seizures, the average seizure severity was Racine score 3.37 ± 0.18 (range, 3–4), and average seizure duration was 97.88 ± 10.20 seconds (range, 50–140 seconds), confirming the risk for post‐traumatic epileptogenesis in the experimental model. It is possible that strain differences, use of younger juvenile rats, which are more susceptible to adverse effects of brain injury, implementation of injury on the day after surgery to minimize neuroprotection due to surgical anesthesia, and inclusion criteria based on apnea duration contributed to greater proportion of rats developing spontaneous seizures compared to earlier studies …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In rats with spontaneous seizures, the average seizure severity was Racine score 3.37 ± 0.18 (range, 3–4), and average seizure duration was 97.88 ± 10.20 seconds (range, 50–140 seconds), confirming the risk for post‐traumatic epileptogenesis in the experimental model. It is possible that strain differences, use of younger juvenile rats, which are more susceptible to adverse effects of brain injury, implementation of injury on the day after surgery to minimize neuroprotection due to surgical anesthesia, and inclusion criteria based on apnea duration contributed to greater proportion of rats developing spontaneous seizures compared to earlier studies …”
Section: Resultsmentioning
confidence: 99%
“…It is possible that strain differences, use of younger juvenile rats, which are more susceptible to adverse effects of brain injury, 40 implementation of injury on the day after surgery to minimize neuroprotection due to surgical anesthesia, and inclusion criteria based on apnea duration contributed to greater proportion of rats developing spontaneous seizures compared to earlier studies. [41][42][43] To transition our findings on TLR4 modulation of excitability in ex vivo slices to in vivo, we examined whether systemic TLR4 antagonism could modify dentate excitability 1 week after injury. Sham and FPI rats were treated with CLI-095 (0.5mg/kg, subcutaneously, for 3 days) starting 20 to 24 hours after injury, and dentate excitability was examined in hippocampal slices 6 to 8 days later.…”
Section: Systemic Tlr4 Antagonism In Vivo Has Opposing Effects On Earmentioning
confidence: 99%
“…The power calculation was based on our previous data indicating that approximately 25% of rats with severe lateral fluid-percussion-induced (FPI) traumatic brain injury (TBI) will have at least one spontaneous seizure (ie, epilepsy) during the 1-month video-electroencephalography (video-EEG) monitoring at the sixth post-TBI month. 13,18,46 Furthermore, the biomarker was expected to have an area under the curve > 0.700 in the receiver-operating characteristic (ROC) analysis. Consequently, we needed at least 22 rats with epilepsy.…”
Section: Correlationsmentioning
confidence: 99%
“…In several pilot studies, we examined and described typical alterations of brain electrical activity observed in rats subjected to penetrating TBI [6][7][8][9]. Despite the fact that a number of labs successfully apply EEG/ECoG techniques to study epileptiform activity in traumatized rats [10,11], the overall number of works currently employing these techniques to study pharmacological neuroprotection remains fairly low [12,13]. However, using EEG for this purpose has several definite advantages.…”
Section: Introductionmentioning
confidence: 99%